2022
DOI: 10.7759/cureus.23322
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Functional Results of Reverse Total Shoulder Arthroplasty and Postoperative Rehabilitation Protocol

Abstract: This retrospective study aims to analyze the clinical and functional results obtained over a seven-year period of performing reverse total shoulder arthroplasty (RTSA) and the subsequent postoperative rehabilitation protocol. MethodsWe analyzed data from 80 patients who were evaluated at a preoperative, as well as monthly postoperative outpatient consultation, until the discharge from the rehabilitation program, using Constant Score (CS). ResultsA comparison of preoperative and postoperative (after rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…A very important and often emphasized element of postoperative management in patients after rTSA is properly and regularly performed physiotherapy. Pereira et al, based on research conducted in 2022, observed that rTSA combined with rehabilitation procedures results in an upward trend in the range of motion of flexion, abduction and the combined movement of abduction with external rotation, and at the same time, it results in a downward trend in the range of combined movement of extension, adduction and internal rotation as well as in the strength of the deltoid muscle [26].…”
Section: Discussionmentioning
confidence: 99%
“…A very important and often emphasized element of postoperative management in patients after rTSA is properly and regularly performed physiotherapy. Pereira et al, based on research conducted in 2022, observed that rTSA combined with rehabilitation procedures results in an upward trend in the range of motion of flexion, abduction and the combined movement of abduction with external rotation, and at the same time, it results in a downward trend in the range of combined movement of extension, adduction and internal rotation as well as in the strength of the deltoid muscle [26].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, several approaches to applying the core components and ideas of rehabilitation are used. 4,[8][9][10][11][12][13] Moffatt et al in a recent review focused on early versus delayed rehabilitation in shoulder arthroplasties (anatomic + reverse). 14 The investigation found no differences in patient-reported or clinician-reported outcomes at 12 months.…”
Section: Introductionmentioning
confidence: 99%